Hospitalizations for mental and behavioral disorders, Northern region, Brazil, from 2017 to 2021 (Research, Society and Development, 2022)
Mental disorder is a syndrome of clinical intellectual, emotional or behavioral disturbance of an individual, with psychological, biological or developmental impairments due to intimate relationships. The present study aimed to make an epidemiological analysis of mental and behavioral disorders in the northern region of Brazil, from 2017 to 2021. This is a descriptive study, with data obtained from the informatics department of the Unified Health System in Brazil. The results showed that the North region contributed with 3.57% of hospitalizations for mental disorders, with Pará being the state that most hospitalized in the region for the disorders addressed in the study interval, with 42%, followed by Rondônia with 18.2%. Thus, this work shows the epidemiological scenario of mental disorders in the North region, serving as a parameter for future research on the topic discussed.